Characteristics of a new UT-type prefabricated joint for rectangular steel tubes under combined axial-moment loading - Menghan Sun; Luyao He; Zailin Yang (PLoS ONE, 2025)
This study proposes a UT-type prefabricated joint incorporating adjustable sleeves (±5 mm tolerance) and an energy-dissipating segment to address the practical demands for construction tolerance management and plasticity assurance. Through systematic static and cyclic loading tests, the paper examines the mechanical behavior of UT-type joints under the combined axial force and bending moment. The results demonstrate that axial force significantly influences joint performance. Specifically, axial tension enhances the initial stiffness by 42.6% (μ = 0.4), while axial compression reduces the yield moment by 24.5%. Cyclic loading tests confirm the joint’s notable energy dissipation capacity. However, high axial forces induce brittle failure risks; thus, practical engineering applications require attention to buckling in the upper connecting plate of the energy-dissipating segment. Additionally, a simplified trilinear restoring force model is proposed, with an error margin of less than 10%. This model adapts to various loading conditions via axial force-dependent parameter adjustments and demonstrates satisfactory accuracy across validations.